2019
DOI: 10.1177/2045894019884516
|View full text |Cite
|
Sign up to set email alerts
|

Severe pulmonary hypertension and reduced right ventricle systolic function associated with maternal mortality in pregnant uncorrected congenital heart diseases

Abstract: Background: Pregnant uncorrected congenital heart disease patients, especially those who already developed pulmonary hypertension, have increased risk for maternal mortality. The pulmonary hypertension severity and right ventricle function may be associated with higher maternal mortality. The study aimed to investigate the mortality rate of pregnant uncorrected congenital heart disease and the impact of pulmonary hypertension severity on mortality. Methods: This is the sub study of COngenital HeARt Disease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
(37 reference statements)
0
10
1
Order By: Relevance
“…Most CHD-related PAH patients (with uncorrected ASD) in Indonesia belonged to the intermediate-risk group, according to the 6MWT results [ 7 19 ]. In Indonesia, pregnant women with PH related to uncorrected CHD have a high risk of maternal mortality (12.5%), which was higher than the previous study by Hartopo et al (10.7%) [ 20 ]. This study indicated that 64.3% patients were diagnosed with CHD at the time of pregnancy [ 20 ].…”
Section: Diagnosis Of Pah In Indonesia and Guideline Implementationmentioning
confidence: 64%
See 2 more Smart Citations
“…Most CHD-related PAH patients (with uncorrected ASD) in Indonesia belonged to the intermediate-risk group, according to the 6MWT results [ 7 19 ]. In Indonesia, pregnant women with PH related to uncorrected CHD have a high risk of maternal mortality (12.5%), which was higher than the previous study by Hartopo et al (10.7%) [ 20 ]. This study indicated that 64.3% patients were diagnosed with CHD at the time of pregnancy [ 20 ].…”
Section: Diagnosis Of Pah In Indonesia and Guideline Implementationmentioning
confidence: 64%
“…In Indonesia, pregnant women with PH related to uncorrected CHD have a high risk of maternal mortality (12.5%), which was higher than the previous study by Hartopo et al (10.7%) [ 20 ]. This study indicated that 64.3% patients were diagnosed with CHD at the time of pregnancy [ 20 ]. It was observed during the study that no antenatal care for CHD condition was done to the patients [ 20 ].…”
Section: Diagnosis Of Pah In Indonesia and Guideline Implementationmentioning
confidence: 64%
See 1 more Smart Citation
“…Due to the high risk of pregnant patients with PAH, clinical practice has been promoting contraception knowledge of PAH women, while improving PAH treatment methods [ 19 ]. Since 1990, some progress has been made in the treatment of PAH in China, and the mortality rate of patients with mild PAH has currently decreased to less than 10%, but the prognosis of patients with severe PAH remains unsatisfactory [ 20 ]. Although studies have shown that medication from early pregnancy can optimize the microcirculation of patients, drugs such as endothelin antagonists leave adverse effects on mothers and fetuses and cannot effectively improve maternal and fetal outcomes [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant patients with uncorrected heart disease increased maternal mortality by 10.7%, and those with heart disease and pulmonary edema increased maternal mortality by 12.5%. The worsening outcome in pregnancy and childbirth of pregnant patients with heart disease and pulmonary edema is largely caused by a compromised cardiovascular system and worsening breathing (Hartopo et al, 2019).…”
Section: Path Analysismentioning
confidence: 99%